Barong Bulu Goak Dalam Kajian Teo Estetika Hindu - Pertu Agung, I Gusti Ngurah (Jurnal Penelitian Agama Hindu, 2025)
Barong Bulu Goak is a unique manifestation of culture and spirituality in Hindu society in Bali. Known for its rare and sacred presence, the Barong Bulu Goak attracts attention because it uses crow feather decoration, which is rarely used in other types of barong. This research aims to explore the theological and aesthetic depth surrounding Barong Bulu Goak in the context of Balinese culture. This research uses a descriptive qualitative approach to explore the symbolic role, ritual and theological meaning of Barong Bulu Goak in Balinese society. The main focus of this research is to explore the Theo-Aesthetic aspects surrounding Barong Bulu Goak, relate it to Hindu theological concepts, and explore how the use of crow feathers as an aesthetic element influences aesthetic perception and experience. In the context of theo-aesthetics, this research explains how Hindu theological concepts related to Brahman and its manifestations in everyday life are combined with aesthetic experiences through performing arts. The results of the research present that Barong Bulu Goak shows a tendency in its appearance and rituals to exude beauty or Ramya Tattwa and also the Suwung Tattwa phase which reflects aspects of Balinese artistic aesthetics. The concept of ramya refers to the integrated beauty of make-up, movement, and rituals that attract attention and radiate feelings of joy and satisfaction in religious ceremonies. Suwung presents quiet moments that provide opportunities for spiritual reflection and deep appreciation of the presence of Barong Bulu Goak in the ritual until the peak of the experience is known as saktibhava, marking the moment where the ceremony participants feel connected spiritually which indicates the existence of Barong Bulu Goak is a creative expression which shows how spiritual and aesthetic life in the Hindu context can combine in a deep experience, giving rise to the power of spirituality in the perception of beauty.